2020
DOI: 10.3390/w12020517
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization and Application of Stanghellini Model for Estimating Greenhouse Cucumber Transpiration

Abstract: Accurate estimation of transpiration (Tr) is important in the development of precise irrigation scheduling and to enhance water-use efficiency in agricultural production. In this study, the air temperature (Ta) and relative humidity (RH) were measured at three different heights (0.5, 1.0, and 1.8 m above the ground near the plant canopy) parameterize aerodynamic resistance (ra) based on the heat transfer coefficient method and to estimate Tr using the Stanghellini model (SM) during two growing seasons of cucum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Findings of this study showed an enhanced ET prediction with the Stanghellini model with a model efficiency (R 2 ) of 0.872 as compared to 0.481 achieved through the Penman-Monteith model [15]. Overestimations of the evapotranspiration rates were observed, and few studies explained the potential cause of these overestimations including the challenging parametrisation of the canopy and aerodynamic resistances and the somewhat non-homogeneous microclimate data collected in greenhouse environments [13]. The Penman-Monteith model assumes homogeneity in collected climatic data which can be appropriate for open field settings but can rather introduce discrepancies for ET estimates in greenhouse mediums.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Findings of this study showed an enhanced ET prediction with the Stanghellini model with a model efficiency (R 2 ) of 0.872 as compared to 0.481 achieved through the Penman-Monteith model [15]. Overestimations of the evapotranspiration rates were observed, and few studies explained the potential cause of these overestimations including the challenging parametrisation of the canopy and aerodynamic resistances and the somewhat non-homogeneous microclimate data collected in greenhouse environments [13]. The Penman-Monteith model assumes homogeneity in collected climatic data which can be appropriate for open field settings but can rather introduce discrepancies for ET estimates in greenhouse mediums.…”
Section: Discussionmentioning
confidence: 69%
“…r R = ρ a C p 4σ(T a + 273.15) 3 (12) The external or aerodynamic resistance r e for the Stanghellini model is defined as shown in Equation (13). N u = 0.37 Gr + 6.92Re 2 0.25 (14) where l represents the characteristic dimension of a leaf (m), λ a is the thermal conductivity, ρ a and C p are the air density (kg m −3 ) and air specific heat capacity (J kg −1 •C −1 ).…”
Section: Stanghellini Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the versatility of the model may be poor as it lacks consideration for the changes in water consumption intensity and greenhouse microenvironment during crop growth and development. In addition, due to the interaction between crop transpiration and the greenhouse microenvironment, the effect of the former on the latter gradually increases with the growth and development of the crops [28]. Therefore, the sensitivity of the crop to the greenhouse microenvironment is different at different growth stages [29].…”
Section: Introductionmentioning
confidence: 99%